(untitled) (Itinera, 2014)
The essay by Claudio Rozzoni Il Riso di Molière. Teatro e impersonalità, which has been published in this magazine, examines the phenomenon of the comedian with particular emphasis on his/her impersonal nature. Starting from Henri Bergson’s ideas, and with particular and frequent reference to Molière’s theatre, Rozzoni takes a first step toward defining the air of impersonality that characterises comedy. The purpose of this work is to further explore the aforementioned idea. This study will start with Rozzoni’s analysis and will subsequently make use of the thoughts of the Franco-American anthropologist René Girard, in order to show the mimetic and undifferentiating character of impersonality. At the end of this study, a religious anthropology of comedy will be outlined: moving from sacrificial rituals to medieval festivals and to the gradual professionalization of the modern era, this work will finally look at the contemporary time, shedding light on the long-existing link between the role of the comedian and that of an expiatory victim.